2012
DOI: 10.1186/ar4050
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical factors and physical examination findings in osteoarthritis of the knee: associations with tissue abnormalities assessed by conventional radiography and high-resolution 3.0 Tesla magnetic resonance imaging

Abstract: IntroductionWe aimed to explore the associations between knee osteoarthritis (OA)-related tissue abnormalities assessed by conventional radiography (CR) and by high-resolution 3.0 Tesla magnetic resonance imaging (MRI), as well as biomechanical factors and findings from physical examination in patients with knee OA.MethodsThis was an explorative cross-sectional study of 105 patients with knee OA. Index knees were imaged using CR and MRI. Multiple features from CR and MRI (cartilage, osteophytes, bone marrow le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…Major strengths of this study are the use of 3.0T MRIs, which were systematically assessed according to the BLOKS scoring system (), a low dropout rate (4%), and high patient adherence. Study limitations include the absence of a “no exercise” control group, the large number of analyzed associations (n = 32), and the lack of contrast used for assessing effusion/synovitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major strengths of this study are the use of 3.0T MRIs, which were systematically assessed according to the BLOKS scoring system (), a low dropout rate (4%), and high patient adherence. Study limitations include the absence of a “no exercise” control group, the large number of analyzed associations (n = 32), and the lack of contrast used for assessing effusion/synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on MRI assessment is included in our previous publication (). In summary, 3.0T MRI scans (General Electric Medical Systems, 5 sequences) of the most affected knee (index knee) were obtained at baseline (i.e., 1–3 weeks prior to the start of the intervention).…”
Section: Methodsmentioning
confidence: 99%
“…Joint degeneration. Several cross-sectional studies reported that radiographic OA (ROA) was associated with lower muscle strength in knee OA (21,24,26,28,31,(57)(58)(59)(60)(61). Although in all joint compartments the presence of ROA was associated with quadriceps weakness, the strongest relation was found when a combination of tibiofemoral (TF) and patellofemoral (PF) ROA was present (57,58).…”
Section: Osteoarthritis-specific Factorsmentioning
confidence: 99%
“…Therefore, for synovitis evaluation by use of non-enhanced MRI (NEMRI), T2 hyperintensity within the Hoffa fat pad is used as a surrogate marker. Using NEMRI and a semiquantitative approach, Knoop et al revealed that quadriceps weakness was associated with synovitis for patients with knee OA [51]. Zhang et al revealed that change in synovitis is associated with fluctuations of knee pain for patients with knee OA [49].…”
Section: Mri Of Synovitismentioning
confidence: 99%